Experiences growing a modern rice cultivar - Begam, Raksya (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
A farmer from Bangladesh describes her experiences growing a modem rice variety.